Analysis and Improvement of Time Frames Management for Ischemic Stroke Services in the Emergency Room at Budi Medika Hospital, Bandar Lampung - Theng, Luther; Jak, Yanuar (Syntax Corporation Indonesia, 2024)
Stroke is a catastrophic disease and a major health problem both in Indonesia and in the world. Stroke causes a high number of morbidities and mortalities. The philosophy of stroke